PENGEMBANGAN FLIPBOOK BERBASIS DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIKIH MATERI QURBAN KELAS V MI DARUL HIKAM KOTA BATU - khoiriyah, rosa nur (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
At elementary school level, fiqh is studied with the aim of ensuring that students are able to practice the provisions of Islamic law properly and correctly as a form of obedience to Islamic teachings, both as a relationship between themselves and Allah SWT, with other people and with the environment. One of the materials taught to students is sacrificial material. Evidence that students have met the learning outcomes is by looking at the students' learning outcomes. Good learning outcomes indicate that learning outcomes have been met, and vice versa. This research uses Research and Development (R&D) research with the ASSURE model. The development steps in this model include: (1) analyze student (conduct an analysis of the student's character), (2) state objects (set goals in learning) (3) select method. media and materials (choosing media and learning methods as well as teaching materials), (4) utilize materials (utilize teaching materials), (5) requile learnest participation (involve students in learning), (6) evaluate and revise (evaluate and revise learning programs ). The results of this research and development are digital-based flipbook learning media products for class V Fiqh subject matter "sacrifices". The media developed received media validation results of 92% with "very feasible" criteria and material validation results of 87.5% with "very feasible" criteria. Apart from that, digital-based flipbook media also received 89.2% assessment results from the attractiveness questionnaire filled out by students so that flipbook media can be said to be an interesting learning media. ABSTRAK Pada jenjang sekolah dasar, fikih dipelajari dengan tujuan agar para peserta didik mampu mengamalkan ketentuan hukum islam dengan baik dan juga benar sebagai wujud ketaatannya menjalankan ajaran islam, baik sebagai hubungan antara dirinya dengan Allah SWT, dengan orang lain maupun dengan lingkungan. Salah satu materi yang diajarkan kepada peserta didik yaitu materi qurban. Bukti bahwa peserta didik telah memenuhi capaian pembelajaran adalah dengan dilihat hasil belajar para siswa. Hasil belajar yang baik menandakan bahwa capaian pembelajaran telah terpenuhi, begitupun sebaliknya. Penelitian ini menggunakan jenis penelitian Research and Development (R&D) dengan model pengembangan ASSURE. Langkah langkah pengembangan pada model ini antara lain: (1) analyze student (melakukan analisis pada karakter peserta didik), (2) state objectivies (menetapkan tujuan dalam sebuah pembelajaran) (3) select method, media and material (memilih media dan metode pembelajaran serta bahan ajar), (4) utilize materials (memanfaatkan bahan ajar), (5) requile learnest participation (melibatkan siswa dalam pembelajaran), (6) evaluation and revise (mengevaluasi dan merivisi program pembelajaran). Hasil penelitian dan pengembangan ini berupa produk media pembelajaran flipbook berbasis digital pada mata pelajaran Fikih kelas V materi “kurban”. Media yang dikembangkan mendapatkan hasil validasi media sebesar 92% dengan kriteria “sangat layak” dan mendapatkan hasil validasi materi sebesar 87,5% dengan kriteria “sangat layak”. Selain itu, media flipbook berbasis digital juga mendapatkan hasil penilaian dari angket kemenarikan yang diisi oleh peserta didik sebesar 89,2% sehingga media flipbook dapat dikatakan sebagai media pembelajaran yang menarik.